2022
DOI: 10.1021/acs.jced.1c00911
|View full text |Cite
|
Sign up to set email alerts
|

Phase Properties and Wetting Transitions of Simple Gases on Graphite─Characteristic Temperatures of Monolayer Adsorbate

Abstract: Computer simulations were performed to study the characteristic transition temperatures of the adsorbate monolayer transitions on graphite and to determine the layering temperatures for higher layers at temperatures less than the bulk triple point temperature. Two models for graphite were studied to examine the effects of finite size of the graphene layer on the evolution of the characteristics of the monolayer, its boundary with the gas phase, and the resulting isotherm and isosteric heat versus loading. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…(1) = 60 K, and it was found that the 2D-triple point temperature is around 47 K, in agreement with the simulation results of Loi et al 30 and the experimental data of Migone et al 41 To further substantiate the transition from a gas-like state to a solid-like state for adsorption at 30 K, we analyzed in detail the isosteric heat as a function of loading, shown in Figure 6. Canonical ensemble simulations give the isosteric heats through the first-order transition from the gas-like state to a solid-like state, and these have a constant value of about 12 kJ/ mol, supporting the boundary growth mechanism proposed earlier from analysis of isotherms and molecular configurations in Figures 3 and 4.…”
Section: Formation Of the Single Layer At 30 Ksupporting
confidence: 85%
See 4 more Smart Citations
“…(1) = 60 K, and it was found that the 2D-triple point temperature is around 47 K, in agreement with the simulation results of Loi et al 30 and the experimental data of Migone et al 41 To further substantiate the transition from a gas-like state to a solid-like state for adsorption at 30 K, we analyzed in detail the isosteric heat as a function of loading, shown in Figure 6. Canonical ensemble simulations give the isosteric heats through the first-order transition from the gas-like state to a solid-like state, and these have a constant value of about 12 kJ/ mol, supporting the boundary growth mechanism proposed earlier from analysis of isotherms and molecular configurations in Figures 3 and 4.…”
Section: Formation Of the Single Layer At 30 Ksupporting
confidence: 85%
“…Although these characteristic temperatures follow the above inequality for each layer, it is interesting to investigate the behavior of each characteristic temperature across different layers. We have established the following inequalities from simulations over a wide range of temperatures with both grand canonical and canonical simulations ,,,, We note that the layering temperature increases for higher layers (eq ) and that the difference between the layering temperature of the first layer and that of the second layer is 34 K, and that the difference between the second and third layers is only 13 K. It is expected that the onset of higher layers will be no longer first order, i.e., layering is no longer distinct; not only because the difference between successive higher layers is smaller, and because of the temperature increase toward the bulk triple point (where thermal fluctuations are greater), but also because there will be a weaker contribution from the graphite potential energy. Furthermore, when multiple layers have been formed on the surface, it is expected that condensation of adsorbate at the junctions between microparticles would interfere with the molecular layering.…”
Section: Results and Discussionmentioning
confidence: 83%
See 3 more Smart Citations